Analisis Perkembangan Agama Islam di Malaysia Sebagai Sumber Pembelajaran Sejarah - Viona Audia Putri; Susnayanti Susnayanti; Reka Seprina (Prabayaksa: Journal of History Education, 2024)
The growth of the Islamic religion reveals Malaysia's Islamic history and civilization. The purpose of this study is to look at the evolution of Islam in Malaysia from historical perspectives. Islam was crucial in defining Malaysian identity and laying the groundwork for the country's social, political, and cultural development. This research examines the history of Islam from prehistoric times to the present, focusing on significant events such as the commencement of the religion's spread throughout the region, the Malay Sultanate, the arrival of Western colonialists, and the establishment of contemporary Malaysia. The approach utilized in this study is a qualitative descriptive method, which is reviewed using data gathering methods in the form of literature reviews. The findings of this study demonstrate how Islam maintains its fundamental beliefs and religious identity while adjusting to the demands of the modern world. Understanding the evolution of Islam in Malaysia can help students learn more about the country's cultural and social dynamics, as well as how it fits into the larger global context.